The Implementation of Therapeutic Communications with Postoperative Patient Satisfaction in Islamic Hospital of Sultan Agung Semarang - Alif Wahdatin; Dyah Wiji Puspita; Muh. Abdurrouf (Jurnal Ners, 2019)
Introduction: Weaknesses in applying therapeutic communication are still a problem for nurses. This affects the quality of nursing services that have an impact on patient satisfaction. The purpose of this study was to identify the relationship between therapeutic communication and postoperative patient satisfaction.Methods: This research method was an analytical survey method used a cross sectional approach. Respondents in this study were postoperative patients who were treated in RSISA inpatient ward with 127 patients.  Sampling technique that use was simple random sampling. The data analysis technique in this study used the Spearman test.Results: The results showed that the majority characteristics of respondents had female 61.4%, age 50-64 (33.8%), employment of private employees 24.4%, senior secondary education 37.0%. The results also showed that most therapeutic communication was in the good category (54.3%) and patient satisfaction in the category was very satisfied (52.8%). The results of this research showed that there was significant relationship between therapeutic communication and postoperative patient satisfaction with p-value 0,000 (p-value <0.05).Conclusion: The implications of this research can be a reference in increasing the ability of nurse therapeutic communication so that patient satisfaction with nursing services increases.